Isolation of short RNAs with homogeneous 3′-ends using quaternary-amine anion exchange chromatography - Li, Zixian; Bilic, Mia; Nagar, Bhushan (Biology methods and protocols, 2024)
Visualizing RNA–protein interactions through structural approaches requires the use of RNA molecules purified to homogeneity. We describe here a simple and effective method, free of acrylamide contamination and without using UV radiation, to separate in vitro synthesized, heterogeneous RNA transcripts (up to ∼15 nucleotides) at single-nucleotide resolution by quaternary-amine anion exchange chromatography. The quality of short RNAs isolated through this method is validated by gel electrophoresis, mass spectrometry, and crystallization with a protein-binding partner.